Helping Families With Fateful Decisions. (4th October 2022) - Yechoor, Nirupama; Rosand, Jonathan
Abstract : Few decisions are more fateful than those we must make on behalf of our loved ones with devastating brain injuries. What would they consider a fate worse than death? In addition, if we think we can intuit an answer to that weighty question with some confidence, what odds might they be willing to take? Would they continue life-sustaining care if there is a 10% chance of achieving recovery? If the most likely outcome is a fate worse than death, should we choose to pursue every medical intervention to ensure survival? These are agonizing decisions. When made with the support of a trustworthy medical team, we can at least emerge with the confidence that we did the best we possibly could for our loved one, guided by best intentions, medical expertise, collaboration, and trust.